Antibioticresistant infection and hydrocephalus: successful resolution of complications and consequences of traumatic brain injury (Case study) (Herald of the National Children's Medical Center, 2025)
The brain is especially protected by the cranial vault, meninges, and blood-brain barrier. Surgical aggression increases the risk of cerebrospinal fluid leakage, which facilitates the penetration of viral and bacterial infections with subsequent meningoencephalitis. We have presented an example of the management of antibiotic-resistant meningoencephalitis and subsequent hydrocephalus by surgical correction. The experience gained, in our opinion, will complement the arsenal for combating this category of disease.
Keywords: craniectomy; cerebrospinal fluid leakage; hydrocephalus; meningoencephalitis